2008
DOI: 10.3174/ajnr.a1099
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Anomalies in CHARGE Syndrome: Imaging Findings of a Potential Major Diagnostic Criterion

Abstract: BACKGROUND AND PURPOSE: CHARGE syndrome is a genetic disorder resulting in the association of multiple congenital anomalies. Although a high prevalence of olfactory anomalies in CHARGE syndrome has been reported in autopsy and functional studies, to our knowledge, such anomalies have not been included among the diagnostic criteria, and their radiographic prevalence has not been assessed. The purpose of this research was to determine the radiographic prevalence of olfactory anomalies in a small sample of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…3 Pachygyria, polymicrogyria, subependymal heterotopias, transmantle cortical dysplasia, and thalamic fusion were all found in this group of patients. There are multiple case reports and small series of olfactory anomalies either isolated or with associated abnormalities [5][6][7][8] ; however, this is largest pediatric cohort reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Pachygyria, polymicrogyria, subependymal heterotopias, transmantle cortical dysplasia, and thalamic fusion were all found in this group of patients. There are multiple case reports and small series of olfactory anomalies either isolated or with associated abnormalities [5][6][7][8] ; however, this is largest pediatric cohort reported.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory nerves should be carefully evaluated in children with sensorineural hearing loss, especially with imaging findings consistent with CHARGE syndrome. 6 The presence of anosmia in patients with CHARGE syndrome can be predictive of associated pituitary dysfunction; however, this association may be difficult to clinically assess in young patients and the presence of olfactory anomalies should prompt an evaluation of pituitary function. 20,21 Panhypopituitarism was present in one of the patients with CHARGE.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the radiologic diagnostic methods, Chalouhi et al 11 reported that anomalies of the olfactory bulbs and tracts might be pathognomonic for CHARGE syndrome and should be included as a major criterion for the diagnosis of this syndrome; Blustajn et al 10 recently reported that these anomalies were the most prevalent features of CHARGE syndrome. The present study showed that basioccipital hypoplasia and basilar invagination are significantly prevalent in the syndrome.…”
Section: (ϫ35)mentioning
confidence: 99%
“…[10][11][12] We encountered a few children with severe hypoplasia of the basiocciput during a radiologic assessment of patients with CHARGE syndrome. Basiocciput hypoplasia results in shortening of the clivus and is always associated with basilar invagination.…”
mentioning
confidence: 99%
“…New diagnostic criteria have been proposed in the past few years (see reference 41 ). Moreover, it has been reported that most if not all CHARGE patients have both olfactory bulb aplasia or hypoplasia and HH, 42,43 that is, the two KS defining features. Consequently, previously reported KS cases associated with congenital heart disease 44 or choanal atresia 45 could in fact represent unrecognised mild CHARGE cases.…”
Section: Differential Diagnosis: Normosmic Idiopathic Hh and Charge Smentioning
confidence: 99%